What is the difference between thus and thusly? - Morana LUKAČ (E-REA)
Usage guides and dictionaries largely agree that thusly was coined for humorous purposes in the mid-nineteenth century in the US as a hypercorrect substitute for thus (Butterfield 2007:157). Most of the prescriptive usage guides treat thusly critically and describe it as “best-avoided” and replaced by thus or they even designate it as a “non-word” (Lukač and Tieken-Boon van Ostade forthcoming).To find out what the acceptability ratings for the word are currently, together with Ingrid Tieken-Boon van Ostade, I conducted an online survey made available between July and September 2015, in which we asked the participants to rate the word on a six-fold acceptability scale (informal speech, formal speech, informal writing, formal writing, netspeak, and unacceptable under any circumstances).In this paper, with the survey findings as my starting point, I aim to establish whether a current change in progress correlates with higher acceptability ratings among younger speakers. I will do so by exploring large-scale corpora consisting of web-based data, the Global Web-Based Corpus (GloWbE) (Davies 2013) and the NOW Corpus (Davies 2013), where a higher number of occurrences of this low-frequency word can be found. I suspect that, in spite of prescriptions against the word’s usage, thusly is slowly gaining status and legitimacy. Moreover, as thusly is assigned American origin, and it is most commonly found in American usage guides (Lukač and Tieken-Boon van Ostade forthcoming), I will explore the frequency of its usage across different varieties of English as well as its meanings in context. All in all, in this paper I aim to shed light on the interplay between the treatment of thusly in prescriptive literature, the changes in speakers’ attitudes, and the variation in its usage.